2010
DOI: 10.1016/j.otohns.2010.08.011
|View full text |Cite
|
Sign up to set email alerts
|

Pneumococcal meningitis post-cochlear implantation: Preventative measures

Abstract: The recent scientific data support the U.S. Food and Drug Administration recommendation of pneumococcal vaccination for the prevention of meningitis in implant recipients. Nontraumatic cochlear implant design, surgical technique, and an adequate fibrous seal around the cochleostomy site further reduce the risk of meningitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 51 publications
0
10
0
2
Order By: Relevance
“…A special population at increased risk for S. pneumoniae meningitis are patients with cochlear implants who were found to have 30 times more the incidence of pneumococcal meningitis than that of an age-matched cohort in the general population in the U.S. 85 Studies have shown that pneumococcal vaccination was effective in preventing meningitis induced via the hematogenous route but not through direct extension from the middle ear. [86][87][88] So the current recommendation is that all current and future recipients of cochlear implants should be immunized against S. pneumoniae. In addition to vaccination, providing chemoprophylaxis to close contacts of patients with H. influenzae and N. meningitidis should be provided to prevent and eradicate carrier state and secondary cases.…”
Section: Preventionmentioning
confidence: 99%
“…A special population at increased risk for S. pneumoniae meningitis are patients with cochlear implants who were found to have 30 times more the incidence of pneumococcal meningitis than that of an age-matched cohort in the general population in the U.S. 85 Studies have shown that pneumococcal vaccination was effective in preventing meningitis induced via the hematogenous route but not through direct extension from the middle ear. [86][87][88] So the current recommendation is that all current and future recipients of cochlear implants should be immunized against S. pneumoniae. In addition to vaccination, providing chemoprophylaxis to close contacts of patients with H. influenzae and N. meningitidis should be provided to prevent and eradicate carrier state and secondary cases.…”
Section: Preventionmentioning
confidence: 99%
“…(2013) found that 13% of elderly CI patients experience flap thinning over long-term follow up, although this is rarely significant enough to require implant removal. Meningitis in the post-surgical CI patient is rare and compliance with CI vaccination protocols, specifically against Streptococcus pneumonia , is crucial at all ages ( Wei et al., 2010 ).…”
Section: Safetymentioning
confidence: 99%
“…This chagrin was also reflected in the ICM 2018 voting, in which only 62% of GA delegates agreed that immunotherapy and immunoprophylaxis can be used to prevent biofilm formation and implant‐associated infections (https://www.ors.org/wp-content/uploads/2019/01/Question-5.pdf). Despite the optimistic rationale written in response to this question, which cites: (i) pre‐clinical evidence, (ii) successful human vaccines against other bacterial pathogens (e.g., Bordetella pertussis, Clostridium tetanii, Corynebacterium diphtheriae , Haemophilus influenzae type b, Neisseria meningiditis , Streptococcus pneumoniae ), and (iii) the specific example of S. pneumoniae vaccines (Prevnar ® , Wyeth Pharmaceuticals Inc. and Pneumovax ® , Merck & Co., Inc.) that are Food and Drug Administration (FDA)‐approved for the prevention of meningitis in cochlear implant recipients, this skepticism in response to immunotherapy and immunoprophylaxis for MSKI is appropriate based on the failure of all clinical trials to date that have evaluated immunizations against S. aureus. …”
Section: Resultsmentioning
confidence: 99%